2015
DOI: 10.1007/s10238-015-0362-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pathological analysis of renal damage in elderly patients with type 2 diabetes mellitus

Abstract: The aim of this study was to investigate the causes and influential factors of renal damage in elderly patients with type 2 diabetes mellitus (T2DM). Clinical data and pathological findings at autopsy of 161 elderly T2DM patients died between October 1994 and August 2011 were retrospectively reviewed. The mean age of these patients was 80.8 ± 8.3 years (range 60-105 years). The incidences of diabetic nephropathy (DN), non-diabetic renal diseases (NDRD), and DN complicated with NDRD were 31.1, 62.7, and 16.2 %,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 21 publications
0
12
0
2
Order By: Relevance
“…Diagnosis of such entities, however, remains challenging even with the CDA due to the variety of lesions and organs involved. These cases often require a combination of all the macroscopic data available and frequently the clinical information, which was not used in our study, to complete the non-conclusive pathological results [2426]. …”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of such entities, however, remains challenging even with the CDA due to the variety of lesions and organs involved. These cases often require a combination of all the macroscopic data available and frequently the clinical information, which was not used in our study, to complete the non-conclusive pathological results [2426]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, other studies of renal biopsy in DM have documented that non-diabetic renal disease (NDRD) plays a significant role in diabetic patients. The reported proportion of NDRD alone ranges from 18.1%–82.9% ( Pavkov et al, 2012 ; Byun et al, 2013 ; Sharma et al, 2013 ; Zhuo et al, 2013 ; Horvatic et al, 2014 ; Zwi et al, 2014 ; Klessens et al, 2016 ; Laranjinha et al, 2016 ; Liu et al, 2016 ; Liu, Tian & Jian, 2016 ) in diabetic patients with renal disease, while that of NDRD superimposed on DN ranges from 7.8%–48.9% ( Oh et al, 2012 ; Pavkov et al, 2012 ; Byun et al, 2013 ; Zhuo et al, 2013 ; Horvatic et al, 2014 ; Zwi et al, 2014 ; Klessens et al, 2016 ; Laranjinha et al, 2016 ; Liu et al, 2016 ; Liu, Tian & Jian, 2016 ). It is suggested that the absence of histopathologic evaluation may lead to a relatively high proportion of NDRD that were misdiagnosed as DN among diabetic patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the previous studies are from Western countries, where the spectrum of renal disease is different from that in China. There are only a few small-sampled, single-centered studies explaining the clinicopathological characteristics of DM related kidney disease in China ( Zhuo et al, 2013 ; Liu et al, 2016 ; Liu, Tian & Jian, 2016 ). To date, comprehensive data on renal biopsy findings in Chinese diabetic patients are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Other studies of renal biopsy in DM have documented that non-diabetic renal disease (NDRD) plays a significant role in diabetic patients. The reported proportion of NDRD alone ranges from 18.1%-82.9% (Pavkov et al, 2012;Byun et al, 2013;Sharma et al, 2013;Zhuo et al, 2013;Horvatic et al, 2014;Zwi et al, 2014;Klessens et al, 2016;Laranjinha et al, 2016;Liu, Tian & Jian, 2016) in diabetic patients with renal disease, while that of NDRD superimposed on DN ranges from 7.8%-48.9% (Oh et al, 2012;Pavkov et al, 2012;Byun et al, 2013;Zhuo et al, 2013;Horvatic et al, 2014;Zwi et al, 2014;Klessens et al, 2016;Laranjinha et al, 2016;Liu, Tian & Jian, 2016). It is suggested that the absence of histopathologic evaluation may lead to a relatively high proportion of NDRD that were misdiagnosed as DN among diabetic patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the previous studies are from western countries, where the spectrum of renal disease is different from that in China. There are only a few small-sampled, single-centered studies explaining the clinicopathological characteristics of DM related kidney disease in China (Zhuo et al, 2013;Liu, Tian & Jian, 2016). To date, comprehensive data on renal biopsy findings in Chinese diabetic patients are lacking.…”
Section: Introductionmentioning
confidence: 99%